Preliminary evaluation of the application of digital smile design in clinical internships for undergraduate students - CHEN Qiuwen, MA Da, JIAN Wenting, LIN Han (Kouqiang yixue)
Objective To investigate the application value of digital smile design in clinical internships for undergraduate students in oral restoration, and to provide a method for clinical teaching of aesthetic restoration of anterior teeth. Methods A total of 18 undergraduate students who participated in clinical internships in the prosthotontics department at the Stomatological Hospital of Sun Yat-sen University from 2021 to 2023 were selected as the research subjects. Traditional oral photography and analysis of the red and white aesthetics of anterior teeth were taught, and digital smile design training was conducted using the anterior tooth aesthetic design module of 3-Shape oral scanning software. Digital smile design would be applied to patients with anterior tooth aesthetic problems. The students wererequired to fill out the evaluation questionnaire. Results The survey evaluation results indicated that digital smile design training could enhance students’ understanding and recognition of the aesthetics of anterior teeth (100%), improve their confidence in anterior teeth cases (88.89%), and also help cultivate students’ systematic thinking in diagnosis and treatment (88.89%), improve clinical photography skills (100%), and enhance their ability to communicate with patients (83.33%) and produce case reports (88.89%). All 18 students completed at least 1 case of anterior teeth aesthetic restoration guided by DSD during clinical practice. Conclusion Digital smile design can improve students’ thinking and abilities of digital system, improve their awareness and understanding of aesthetic restoration of anterior teeth, and has application prospects in clinical practice training of oral restoration.